2012
DOI: 10.1136/bmjopen-2011-000362
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: Ho Chi Minh City Youth Cohort—changes in diet, physical activity, sedentary behaviour and relationship with overweight/obesity in adolescents

Abstract: ObjectivesThe Ho Chi Minh Youth cohort study aimed to assess the change in nutritional status; indicators of adiposity; diet; physical activity and sedentary behaviours; home, neighbourhood and school microenvironments and their complex relationships in adolescents in urban areas of Ho Chi Minh City.DesignProspective 5-year cohort.SettingSystematic random sampling was used to select 18 schools in urban districts.ParticipantsChildren were followed up over 5 years with an assessment in each year. Consent, from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
5
24
1
1
Order By: Relevance
“…When the IDF, Cook and the De Ferranti definitions were applied, we found that the prevalence of MetS was higher in Vietnamese adolescents than that reported for adolescents in Hong Kong (Kong et al, 2008), South Korea (Park et al, 2009), China (Li et al, 2008;Yi-Qun and Cheng-Ye, 2008), and India (Singh et al, 2007). The high prevalence of MetS among adolescents in our study may be because the sample investigated came from a setting where there have been rapid changes in socio-economic status and lifestyles which resulted in increases of overweight/obesity and decreases of physical activity (Hong et al, 2007;Trang et al, 2012), while national samples were used in other Asian studies (which included both urban and rural populations). The factor analysis showed that obesity could explain the highest proportion of metabolic components confirming the strong association between obesity factor and MetS and the important role of this factor in MetS, as consistently seen in other studies (Ghosh, 2007;Ng et al, 2007).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…When the IDF, Cook and the De Ferranti definitions were applied, we found that the prevalence of MetS was higher in Vietnamese adolescents than that reported for adolescents in Hong Kong (Kong et al, 2008), South Korea (Park et al, 2009), China (Li et al, 2008;Yi-Qun and Cheng-Ye, 2008), and India (Singh et al, 2007). The high prevalence of MetS among adolescents in our study may be because the sample investigated came from a setting where there have been rapid changes in socio-economic status and lifestyles which resulted in increases of overweight/obesity and decreases of physical activity (Hong et al, 2007;Trang et al, 2012), while national samples were used in other Asian studies (which included both urban and rural populations). The factor analysis showed that obesity could explain the highest proportion of metabolic components confirming the strong association between obesity factor and MetS and the important role of this factor in MetS, as consistently seen in other studies (Ghosh, 2007;Ng et al, 2007).…”
Section: Discussioncontrasting
confidence: 79%
“…This sample was recruited for a cohort study started in 2004 (Trang et al, 2012). The study was approved by the ethics committee of Pham Ngoc Thach University of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…The data examined in this paper is from the Ho Chi Minh City Youth Cohort, 13 a longitudinal study from 2004 to 2009 that examined the magnitude and change in overweight and obesity and the changes in diets, physical activity and sedentary behaviours of adolescents in Ho Chi Minh City, Vietnam. A representative sample of 759 adolescents from 18 schools in urban districts Ho Chi Minh City was selected using systematic sampling.…”
Section: Methodsmentioning
confidence: 99%
“…The sampling methods have been described elsewhere. 13 Children were followed up over 5 years until the end of senior high school with an assessment in each year, including anthropometry, dietary intake and dietary behaviours, physical activity and sedentary behaviours, family social and physical environment, school environment, socioeconomic status and parental characteristics. While the participants were in junior high schools, data were collected by class surveys, but individual follow-up contact was used when the study participants moved to senior high school.…”
Section: Methodsmentioning
confidence: 99%
“…We added additional literatures from hand-search, with citations in a metaanalysis. 18) We found 8 Asian cohort studies [19][20][21][22][23][24][25][26] observing cardiovascular risk factors and their effects on CVD in childhood or adolescent populations ( Table 2).…”
Section: Selection Of the Cohortsmentioning
confidence: 99%